First‐line atezolizumab monotherapy in patients with advanced BRAFV600 wild‐type melanoma. (15th February 2021) - de Azevedo, Sergio Jobim; de Melo, Andreia Cristina; Roberts, Louise; Caro, Ivor; Xue, Cloris; Wainstein, Alberto
Abstract: Anti‐programmed death‐1 agents are an established option for advanced melanoma, but the anti‐programmed death‐ligand 1 (anti‐PD‐L1) antibody atezolizumab, an agent approved for the treatment of multiple solid tumors, was not previously evaluated. This phase 1b study cohort (NCT03178851; cohort C) evaluated first‐line atezolizumab 1, 200 mg every 3 weeks in adults with BRAF V600 wild‐type, histologically confirmed, advanced or metastatic melanoma. The co‐primary end points were confirmed objective response rate (ORR) per Response Evaluation Criteria in Solid Tumors v1.1 and disease control rate (DCR = complete response [CR] +partial response [PR] +stable disease [SD] at 16 weeks). Of 52 enrolled patients, most had lactate dehydrogenase levels lower than the upper limit of normal (77%) and PD‐L1‐positive tumors (55%). Investigator‐assessed confirmed ORR was 35% (95% CI, 22%‐49%) and included three CRs (6%) and 15 PRs (29%); DCR was 46%. Median investigator‐assessed progression‐free survival was 3.7 months (95% CI, 2.1–7.3). The most common any‐grade adverse events were anemia (27%), headache (19%), hypertension (19%), constipation (17%), diarrhea (17%), hypothyroidism (17%), asthenia (15%), and pain in extremity (15%). First‐line atezolizumab monotherapy is safe and tolerable and has antitumor activity in patients with BRAF V600 wild‐type advanced or metastatic melanoma.